TEACHING WRITING THROUGHT DICTOGLOSS - Ratna Sari Dewi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
The objective of this study is to help students in developing their ideas in writing due to their difficulties to arrange ideas. Although they do have ideas, they cannot structure their ideas well in their papers. Several factors could cause this problem such as lack of vocabulary and knowledge or strategies in arranging ideas in papers. Another factor is unclear explanation and insufficient guidance from the teachers. Based on literature review, dictoglos can be a guide for students to develop their ideas in writing. It is a teaching technique which incorporates various activities such listening, taking notes, discussing, and reconstructing which have some standard procedures and variations. English as an international language has been known all over the world. People cannot deny it, because many countries use and learn the language. The fact shows that the language is used as a second or a foreign language in each country in the world. Many people learn it to get involved in the world globalization era, where English in written or oral form of communication is used. Therefore, it is a must for people to learn English. Whether they are students, worker, or other occupations that they belong to, they must study English. It can be learned through learning at school, in a course, or in their own ways. People must learn the language skills in order to master English well. The journey of the learning could be similar to a child learning to walk where he may fall down to the floor and get up to stand again and learn to walk continuously so that he can walk well. It is also the same when we learn a language. We must start from listening, speaking, reading and writing. The four language skills should be learned continuously and patiently. Writing as one of the language skill at any level of education that has to be mastered is rather difficult than other skills. Students feel difficult to arrange their ideas in papers. Actually they have ideas but it is hard for them to deliver it into their paper or they have many ideas but they cannot choose what ideas should be chosen to develop. It happens because they have lack of vocabulary, cannot arrange the ideas correctly, berita terkini internasional do not know how to develop their ideas. This could happen because there is no clear enough information from the teacher. It is also possible that the teacher do not teach well. In addition to teachers, it should be acknowledged that there are many other factors that cause the inability of students to write in English. Because some problems above, the writer wants to give an alternative solution to overcome the problem that is an approach to teach writing. It is hoped that the students have ability to develop their ideas in writing. The approach is called Dictogloss. In this approach students is trained to write their elaboration of one idea or improve simply an idea or a topic chosen by a teacher or they choose it freely from their own.